ANALISIS SUMBER INFORMASI DAN KAPASITAS PETANI DI DESA LAMBUSA KECAMATAN KONDA KABUPATEN KONAWE SELATAN - Maryana Maryana; Iskandar Zainuddin Rela; Ima Astuty Wunawarsih (Universitas Halu Oleo, 2023)
This study aims to determine the utilization of information sources in increasing the capacity of farmers owned by vegetable farmers in Lambusa Village, Konda District, Konawe Selatan District. This research was conducted from December 2022-January 2023. The selection of research locations was carried out purposively (intentionally). The sampling technique is through simple random sampling technique, using descriptive statistical analysis and inferential statistics using the Rank Spearman formula with the help of SPSS software. The results showed that vegetable farmers' use of information sources, such as conventional media, non-conventional media (new media), agricultural extension workers, and motivator farmers, was in the moderate category, with a total average score of 2.58. Meanwhile, the capacity of vegetable farmers, which includes aspects of technical ability, ability to solve problems, planning ability, evaluation ability, environmental adaptability, and partnering ability, is quite varied, from the medium to high category. The role of extension workers in facilitating vegetable farmers to access and use communication technology needs to be increased so that the competence of farmers continues to increase.